Pengaruh Kepuasan Kerja, Keterlibatan Kerja dan Komitmen pada Organisasi Terhadap Turnover Intentions Di PT Sumber Purnama Sakti Mataram - Sulhan Hadi; Nurul Hidayati Indra Ningsih; Lalu Hendra Maniza (JUPE : Jurnal Pendidikan Mandala, 2019)
This research is entitled The Influence of job satisfactions, job invlopment and organizational commitment on the turnover intentions at PT Sumber Purnama Sakti Mataram. The goals of this research are to identify the partial and simultant significances of the influence of job satisfactions, job invlopment and organizational commitment and to identify which of the  variables has the most dominant influence. This research is causality by using sensus sampling method. The model of analysis applied in this research is multiple linier regression analysis where this model is used after testing classical assumptions, including multicollinearity, autocorrelation, and heteroscedasticity. The results of this research show, it can be identified that job satisfactions, job invlopment and organizational commitment have significant influences on the turnover intentions. with contribution equal 64 %. Analyzed partially, job satisfactions has the most dominant influence on turnover intentios